Affective computational interfaces - Venturelli, Suzete (2019)
The following text describes the development of affective computer interfaces that seek to provoke visual, tactile, gustatory and olfactory interactions, a process by which an external or internal stimulus causes a specific reaction that produce a perception, considering that in the deleuzian and guattarian sense (1992), an idea can thoroughly cross creative activities. For the authors, an idea arises in three distinct forms: (1) at one moment arises; (2) in the philosophical context; (3) in the form of concepts; in another moment, it appears in the artistic production of visual artists, in which artist invents perceptions, and it also occurs with musicians because according to the authors, the musician creates affections. Considering this and artistic and design computational production, we describe below the results of collaborative research that has in common the poetics of interactivity, provided by computational processes and methods that approach different ideas involving affective cartography, body, art, nature and artificial life, wearable computers and emergency.